2019
DOI: 10.1136/bmjopen-2019-030619
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of burnout and its associations with learning environment and learner factors among psychiatry residents within a National Psychiatry Residency Programme

Abstract: BackgroundMultiple studies have reported high burnout rates among residents, including psychiatry. There is a paucity of studies examining the relationship between burnout and learning context, stress levels, resilience, stigma in healthcare providers and coping methods concurrently within the same cohort.ObjectiveWe examined the rate of burnout among our psychiatry residents in a cross-sectional study and hypothesised that burnout is associated with poorer perception of learning environment, greater perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…Residents with burnout had greater stress levels and worse perception of the learning environment (p < 0.001) [7]. Consistent with anticipated personal effects of shame, the burnout group was less willing to disclose or seek help, employing greater active-avoidance coping mechanisms [7]. This avoidance of help and introversion in the setting of burnout could be more troublesome than previously described-a positive culture and learning environment can mitigate these concerns.…”
Section: Culture Introversion and Self-valuationmentioning
confidence: 71%
See 2 more Smart Citations
“…Residents with burnout had greater stress levels and worse perception of the learning environment (p < 0.001) [7]. Consistent with anticipated personal effects of shame, the burnout group was less willing to disclose or seek help, employing greater active-avoidance coping mechanisms [7]. This avoidance of help and introversion in the setting of burnout could be more troublesome than previously described-a positive culture and learning environment can mitigate these concerns.…”
Section: Culture Introversion and Self-valuationmentioning
confidence: 71%
“…The importance of workplace culture is also addressed in a cross-sectional study of burnout and its associations with the learning environment of 93 psychiatry residents-55% of whom met Oldenburg Burnout Inventory burnout criteria [7]. Residents with burnout had greater stress levels and worse perception of the learning environment (p < 0.001) [7].…”
Section: Culture Introversion and Self-valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the failure of the system contributed to 80% of burnout factors (Moffic, 2019). Furthermore, in a cross-sectional study in Singapore, burnout had also been associated with higher stigma in residents' help-seeking behaviour and was related to environment and learner factors including stigma, resilience, and coping mechanism (Chew et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…32 Trainees in the first 5 years after graduation are at a greater risk of burnout if they possess the aforementioned characteristics. 33 Patient factors that can also lead to burnout among doctors. Examples would include patients and relatives with unrealistic expectations, deterioration in the patient's health and aggressive patients.…”
Section: Burnoutmentioning
confidence: 99%